Metabolite 2-aminoadipic acid: implications for metabolic disorders and therapeutic opportunities - Shi, Weiyan; Yang, Zhiqiang; Fu, Pengbin; Yang, Yang (Frontiers in Pharmacology, 2025)
Previous evidence has indicated that the role of 2-aminoadipic acid (2-AAA), a derivative of lysine catabolism, in mediating specific detrimental effects on glial cells, notably inhibiting astrocyte activation. In addition, intrathecal administration of 2-AAA has demonstrated significant efficacy in relieving mechanical hyperalgesia. With the growing application of metabolomics in biomedical research, substantial evidence now underscores 2-AAA’s pivotal role in regulating glucose and lipid metabolism. As a novel biomarker, 2-AAA is linked to increased susceptibility to diabetes and has emerged as a critical regulator of glucose homeostasis. This review explores recent advancements in understanding 2-AAA’s potential therapeutic applications, particularly in the context of metabolic diseases such as diabetes, obesity, and atherosclerosis. It also addresses existing research gaps and outlines future directions for developing 2-AAA-based therapies.